Right To Genital Integrity: Law, Limbo and The Status of Intersex Children in India - Rajam, Shardha; Banerjee, Atreyo (Columbia Journal of Gender and Law, 2022)
As the movement for recognizing queer rights in India gains momentum, it is critical to evaluate the rights of a particularly neglected group within the LGBTQIA+ community: intersex children. Since 2018, the Indian Supreme Court has decriminalized consensual adult same-sex relationships and has recognized the right to privacy—including decisional and bodily privacy—as a fundamental right guaranteed by the Indian Constitution. However, even after these crucial decisions, intersex children are still subject to medically unnecessary surgeries without their consent. Many suffer long term consequences from such disentitlement. In this Article we examine the rights of children from an ethical and legal perspective in the Indian context. Drawing on classical, feminist, and queer bioethics frameworks, we briefly review the ethical violations inherent in performing genital surgeries on intersex children without their consent. We analyze India’s international legal obligations and argue that those obligations fill a significant gap in India’s jurisprudence on sexual minorities. We also analyze the domestic legal framework, studying key decisions of various high courts, including the Indian Supreme Court, that have recognized the right to self-determination of gender identity. Finally, we suggest possible alterations to the current legal framework that, if implemented, will help further legal recognition of the rights of intersex children.